On a Newton-Kurchatov-type Iterative Process. (2nd January 2016) - Hernández-Verón, M. A.; Rubio, M. J.
ABSTRACT: Newton's method and Kurchatov's method are iterative processes known for their fast speed of convergence. We construct from both methods an iterative method to approximate solutions of nonlinear equations given by a nondifferentiable operator, and we study its semilocal convergence in Banach spaces. Finally, we consider several applications of this new iterative process.